2007
DOI: 10.1038/nature06009
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for synthesis of inflammatory mediators by human leukotriene C4 synthase

Abstract: Cysteinyl leukotrienes are key mediators in inflammation and have an important role in acute and chronic inflammatory diseases of the cardiovascular and respiratory systems, in particular bronchial asthma. In the biosynthesis of cysteinyl leukotrienes, conversion of arachidonic acid forms the unstable epoxide leukotriene A4 (LTA4). This intermediate is conjugated with glutathione (GSH) to produce leukotriene C4 (LTC4) in a reaction catalysed by LTC4 synthase: this reaction is the key step in cysteinyl leukotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
123
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 25 publications
8
123
0
Order By: Relevance
“…First, we have shown that all cellular LTC 4 synthase is associated with FLAP (19) and that LTC 4 synthase is likely to be enriched in the outer nuclear membrane (10). Second, structural studies have indicated that both FLAP and LTC 4 synthase must exist as independent homotrimers (16,24,25). When combined with our results, this indicates that LTC 4 synthase and FLAP interact at a site distinct from the site where 5-LO and FLAP interact.…”
Section: Discussionsupporting
confidence: 61%
“…First, we have shown that all cellular LTC 4 synthase is associated with FLAP (19) and that LTC 4 synthase is likely to be enriched in the outer nuclear membrane (10). Second, structural studies have indicated that both FLAP and LTC 4 synthase must exist as independent homotrimers (16,24,25). When combined with our results, this indicates that LTC 4 synthase and FLAP interact at a site distinct from the site where 5-LO and FLAP interact.…”
Section: Discussionsupporting
confidence: 61%
“…Initial structural characterization of the MAPEG family was done using electron crystallography and showed that the members contain four transmembrane helices and are organized as trimers (8,9). This was later confirmed by the X-ray crystal structures of FLAP (10) and LTC 4 synthase (11,12). There are also low-resolution 3D electron crystallography structures of MGST1 and mPGES-1 (13,14).…”
mentioning
confidence: 86%
“…8 n-Alkyl-b-D-maltosides (C n G 2 ), which are in the focus of the present study, have been used in many cases as solubilizing agents to achieve membrane protein crystallization. Representative examples of a successful application of C 12 G 2 are photosystem I (PSI) 9 and photosystem II (PSII) [10][11][12] as well as the cytochrome (cyt) b 6 f complex 13 of oxygenic photosynthesis, a bacterial multidrug efflux transporter, 14 a cyt c quinol dehydrogenase, 15 a human leukotriene C 4 synthase, 16,17 and the rotor of V-type Na + -ATPase. 18 The homologous detergent C 11 G 2 was used in the case of the yeast cyt bc 1 complex, 19,20 C 10 G 2 for a glutamate transporter, 21 and C 8 G 2 for a chloride channel.…”
Section: Introductionmentioning
confidence: 99%